Immune B cell responsiveness to single-dose intradermal vaccination against Mycoplasma hyopneumoniae. (December 2021) - Martelli, Paolo; Saleri, Roberta; Andrani, Melania; Cavalli, Valeria; De Angelis, Elena; Ferrari, Luca; Borghetti, Paolo
Abstract: Mycoplasma hyopneumoniae is a major pathogen affecting pig herds and vaccination is the most utilized approach, despite providing partial protection. Age at vaccination, the delivery route, and vaccination protocol can influence vaccine efficacy. The influence of age and the presence of maternally-derived antibodies at vaccination on single-dose needle-less intradermal (ID) administration of an inactivated bacterin-based vaccine (Porcilis® M Hyo ID Once) were assessed in conventional pigs under field conditions. The induction of IgA+ and IgG+ B cell responses and the expression of the activation markers TLR2, TLR7, CCR9, and CCR10 were determined in PBMC. Vaccination at 4 weeks efficiently elicited an anamnestic antibody response associated with TLR2 and TLR7 upregulation. Although animals vaccinated at 1 week did not show seroconversion and a recall response upon infection, the responsiveness of Mycoplasma -recalled IgA+ B cells suggests the activation of mucosal immune cells after vaccination and infection. Vaccination at 1 week induced TLR2, TLR7, and CCR9 upregulation, suggesting the potential for systemic and local activation of immune cell trafficking between blood and target tissues. Vaccination at 4 weeks induced a CCR10 increase, suggesting that recalled IgA+ and IgG+ B cells can display an activated status upon infection. The antibody response after Mycoplasma infection in 4-week-old ID-vaccinated pigs was associated with TLR2 and CCR10 increases, confirming the potential use of this vaccination schedule for the safe and efficient delivery of single-dose M. hyopneumoniae vaccines. ID vaccination, especially at 4 weeks, was associated with a great degree of protection against enzootic pneumonia (EP)-like lung lesions. Highlights: ID vaccination at 4 weeks elicited a humoral response associated with TLR2 and TLR7 up-regulation. Vaccination at 4 weeks induced Mycoplasma -recalled IgA+ and IgG+ B cells, and CCR10 up-regulation. ID vaccination at 1 week stimulated IgA+ B cells and TLR2, TLR7, and CCR9 increases . ID vaccination was associated with a great protection against EP-like lung lesions.